212k views
2 votes
Edna says that when (x - 2)2 = 9, that x - 2 = 3. Use complete sentences to explain whether Edna is correct. Use specific details in your explanation.

2 Answers

3 votes
Assuming the given equation is (x-2)^2 = 9, Edna is partially correct. Saying x-2 = 3 is halfway there in terms of getting the ful solution. She forgot about the minus form of the plus minus. If (x-2)^2 = 9, then applying the square root to both sides leads to these two equations: x-2 = 3 or x-2 = -3. So we have a plus 3 and then a minus 3.
User Swartz
by
5.5k points
6 votes

Answer:x=5,-1

Explanation:

Edna says that when \left ( x-2\right )^2=9[/tex]

then x-2=3

such that x=5

but this is not true as when we put the value of x in equation then it will not satisfy the equation.

It can be solved by taking the terms either on LHS or RHS


\left ( x-2\right )^2-9=0


x-2=\pm 3

x=5

x=-1

User Sagar Ranglani
by
5.9k points